Copper porphyrin catalyzed esterification of C(sp3)–H via a cross-dehydrogenative coupling reaction. (12th April 2017) - Wang, Hua-Hua; Wen, Wei-Hong; Zou, Huai-Bo; Cheng, Fan; Ali, Atif; Shi, Lei; Liu, Hai-Yang; Chang, Chi-Kwong
Abstract : Copper porphyrin was an efficient catalyst for the direct esterification of C(sp 3 )–H bonds using DTBP as an oxidant. Abstract : The crystal structure of 5, 10, 15, 20-tetra(ethoxycarbonyl)porphyrin copper(ii ) showed that its central copper has a six-coordinate structure. An efficient copper porphyrin-catalyzed cross-dehydrogenative coupling (CDC) esterification reaction between C(sp 3 )–H and carboxylic acids using di- tert -butyl peroxide (DTBP) as an oxidant was established. The kinetic isotope effect (KIE) indicated that C(sp 3 )–H bond cleavage was the rate-determining step of this CDC reaction.